Humility, stressful life events, and psychological well-being: Findings from the landmark spirituality and health survey. Issue 5 (2nd September 2016) - Krause, Neal; Pargament, Kenneth I.; Hill, Peter C.; Ironson, Gail
Abstract : A growing body of research suggests that people who are more humble tend to enjoy better physical and mental health than individuals who are less humble. The next step in moving this literature forward involves explaining and empirically demonstrating how the potentially beneficial effects of humility arise. The purpose of this study is to address this issue by seeing whether humility buffers the effects of stressful life events on four measures of well-being: happiness, life satisfaction, depressed affect, and generalized anxiety disorder. Data from a new nationwide survey ( N = 3010) suggest that the magnitude of the negative relationship between stressful life events and all four measures of well-being is reduced among people who are more humble. The theoretical implications of these findings are discussed.